A Low-Cost OMR Solution for Educational Applications - Hui Deng; Feng Wang; Bo Liang (2008 IEEE International Symposium on Parallel and Distributed Processing with Applications, 2008)
Optical mark recognition (OMR) is a traditional data input technique and an important human computer interaction technique which is widely used in education testing. Aimed at the drawbacks of current OMR technique, a new image-based low cost OMR technique is presented in the paper. The new technique is capable of processing thin papers and low-printing precision answer sheets. The system key techniques and relevant implementations, which include the image scan, tilt correction, scanning error correction, regional deformation correction and mark recognition, are presented. This new technique is proved robust and effective by the processing results of large amount of questionnaires.